Identification of pathogenic fungi - Campbell, Colin K. (Wiley-Blackwell, 2013)
"A fully updated edition of this highly regarded textbook, incorporating new colour photographs of key species and their microscopic features, information on the latest antifungal drugs, and updated taxonomic information. Endorsed by the Health Protection Agency and written by world renowned experts in medical mycology"--Provided by publisher.